Pengaruh Harga dan Kemudahan Bertransaksi terhadap Minat Konsumen Menggunakan QRIS pada Warung Nasgor Mas Adi di Jalan Veteran Rantauprapat - Harahap, Fitri Yani; Ulya, Basyarul; Hasibuan, Midrawati (VISA: Journal of Vision and Ideas, 2025)
This research aims to find out whether the perceived usefulness of QRIS and the convenience of QRIS have a significant effect on the efficiency of digital payments at the Mas Adi fried rice stall on Jalan Veteran Rantau Perapat. This research uses a quantitative approach. The population of this research is the local community with a sample size of 100 respondents. The sampling technique used in this research was Non Probability Sampling using purposive sampling. The data collection technique in this research is by using a questionnaire. The data that has been obtained is then processed using the SPSS version 15.0 application. Data processing and analysis techniques include instrument testing, classical assumption testing, multiple regression analysis and hypothesis testing. From the results of simultaneous hypothesis testing on the variables Usefulness of QRIS and Ease of QRIS, the calculated F value (96.947) > F table (3.09) was obtained, with a significance value of 0.000 < 0.05, meaning that the Benefits of QRIS and Ease of QRIS simultaneously (together) have a significant influence on Digital Payment Efficiency.Apart from that, from the results of the determination test, it is known that the coefficient of determination value in the R Square column is 0.667, meaning that the QRIS Benefits and QRIS Ease variables have an influence of 66.7% on the Digital Payment Efficiency variable, while 33.3% is influenced by other variables not explained in this research. For the partial QRIS Benefit variable, t count (4.269) > t table (1.988), has a significant effect on Digital Payment Efficiency. The QRIS Convenience variable partially obtained t count (6.538) > t table (1.988) has a significant effect on Digital Payment Efficiency.